Peran Mediasi Work-Life Balance Terhadap Job Attitude Perawat Rawat Inap Rumah Sakit Swasta Tipe B di Jakarta Utara - Marshella Synthia; Rina Anindita; Ratna Indrawati (Jurnal Health Sains, 2022)
Hospitals need nurses with a high job attitude because nurses will contribute greatly in providing quality and professional services to patients. So hospital management needs to know what factors support the formation of job attitudes in nurses. This study is an associative causality study with a cross-sectional design and a quantitative approach.This study aims to analyze the effect of organizational climate and job demand on the job attitude of inpatient nurses through work-life balance as an intervening variable. This research uses a quantitative approach and survey method using a questionnaire. The population is all inpatient nurses who work in type B private hospitals in North Jakarta, totaling 70 people. The sampling technique was using saturated samples, so that a sample of 70 respondents was obtained. Methods of data analysis using statistical software software. Research results: Organizational climate, job demand, and work-life balance have a significant and simultaneous effect on the job attitude of inpatient nurses in type B private hospitals in North Jakarta; The work-life balance variable has the most influence on the job attitude of inpatient nurses at a type B private hospital in North Jakarta, compared to the other two variables. The findings in this study can be used as input for hospital management to develop strategies as an effort to improve work-life balance and job attitude in